2018
DOI: 10.3390/genes9120568
|View full text |Cite
|
Sign up to set email alerts
|

Segmental and Tandem Duplications Driving the Recent NBS-LRR Gene Expansion in the Asparagus Genome

Abstract: Garden asparagus is an important horticultural plant worldwide. It is, however, susceptible to a variety of diseases, which can affect the potential yield, spear quality, and lifespan of production fields. Screening studies have identified resistant germplasm. The genetic resistance is usually complex, and the genes underlying that resistance are still unknown. Most often, disease resistance is determined by resistance genes (R). The most predominant R-genes contain nucleotide binding site and leucine-rich rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 62 publications
(71 reference statements)
1
9
0
Order By: Relevance
“…Genome-wide identification and evolutionary analysis has been performed in many angiosperms in the past 20 years (Bai et al, 2002;Meyers et al, 2003;Shao et al, 2016Shao et al, , 2019Zhang et al, 2016;Neupane et al, 2018a). Several evolutionary features have been documented, including frequent tandem duplication for gene expansion, cluster organization on the chromosome, rapid species-specific gene loss, and duplication (Meyers et al, 2003;Gu et al, 2015;Shao et al, 2016;Die et al, 2018;Song et al, 2019). However, most of the previous studies have concentrated on dicots, especially the rosid lineage of the angiosperms.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide identification and evolutionary analysis has been performed in many angiosperms in the past 20 years (Bai et al, 2002;Meyers et al, 2003;Shao et al, 2016Shao et al, , 2019Zhang et al, 2016;Neupane et al, 2018a). Several evolutionary features have been documented, including frequent tandem duplication for gene expansion, cluster organization on the chromosome, rapid species-specific gene loss, and duplication (Meyers et al, 2003;Gu et al, 2015;Shao et al, 2016;Die et al, 2018;Song et al, 2019). However, most of the previous studies have concentrated on dicots, especially the rosid lineage of the angiosperms.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the extensively investigated plant R genes contain NBSs 35 . The A. officinalis genome contains 49 different NBS R genes 36 . In this study, we identified 76 nonredundant R genes in the A. setaceus genome, which was greater than the number in A. officinalis.…”
Section: Discussionmentioning
confidence: 99%
“…NLR genes in many plant species are present in large, tandem arrays, which are frequently located on the ends of chromosomes, far from the pericentromeric suppression of recombination [15,16,18,20,21,22,23,24]. Ectopic crossovers are often invoked as a likely mechanism to generate NLR gene diversity in these clusters [16,20,82].…”
Section: Discussionmentioning
confidence: 99%
“…Genomic and comparative evolutionary analyses have been employed to characterize the genetic architecture and structural evolution of NLR genes. Across many plant species, traits such as the number of NLR genes, their locations within the genome, and patterns of deletion, duplication, and divergence have been probed to reveal a history of how gene family members have expanded and diverged (e.g., [1,3,14,15,16,17,18,19,20,21,22,23,24,25]). In A. thaliana , these genome-wide studies have found evidence for genomic clustering of 50%–70% of NLR genes [1].…”
Section: Introductionmentioning
confidence: 99%